Sentence comprehension and production in children with cochlear implants: Errorless procedures and equivalence-based instruction - Neves, Anderson Jonas das [UNESP]; Almeida-Verdu, Ana Claudia Moreira [UNESP]; Silva, Leandra Tabanez do Nascimento; Moret, Adriane Lima Mortari; de Souza, Deisy das Graças (Wiley, 2023)
Research supports equivalence-based instruction (EBI) and matrix training for increased listening and speaking skills in children with cochlear implants (CI). We incorporated errorless procedures to optimize the EBI and evaluated the effects on the auditory comprehension and verbal responding at-sentences level in six CI children who were readers and showed inaccurate tacting. Subject-verb-object sentences were arranged in two matrices; diagonal combinations were trained and evaluated non-diagonal combinations. EBI included stimulus fading and exclusion to directly teach the dictated sentence-picture matching; written-sentences construction upon dictation also was taught. Probes assessed the derived stimulus-stimulus and stimulus-response relations. All participants learned the auditory-visual discriminations and the exclusion resulted in fewer errors than on a stimulus fading procedure. Five participants formed equivalence classes and increased verbal responding to equivalent stimuli, especially pictures tacting. They also showed recombinative generalization for both matrices. Professionals can incorporate errorless procedures to EBI for improving sentence comprehension, tacting, and productivity in CI children.
Keywords: cochlear implant; equivalence-based instruction; errorless procedures; matrix training; sentences